ANALYSIS OF MUSCLE ACTIVITY DURING THE BENCH PRESS EXERCISE PERFORMED WITH THE PRE-ACTIVATION METHOD ON STABLE AND UNSTABLE SURFACES (Kinesiology, 2017)
This study compared the EMG activity of the upper limb and shoulder girdle muscles in a resistance training session involving the pre-activation method in stable and unstable conditions. Fourteen healthy male volunteers (age 22.5±2.4 years; body height 173.6±7.10 cm; body mass 76.03±9.02 kg) performed under three exercise conditions in a randomized order: a) barbell bench press, b) stable dumbbell fly and barbell bench press, and c) unstable dumbbell fly and barbell bench press. Subjects performed 10 repetitions of stable or unstable dumbbell fly at 30% of 1RM, and barbell bench press was executed at 60% of 1RM until concentric failure. The 1RM test was performed in both exercises and, on the case of dumbbell fly, on both surfaces. EMG-signals from the pectoralis maior (PM), deltoid anterior (DA), triceps brachii (TB) and serratus anterior (SA) were acquired. Two-way ANOVA for repeated measures indicated that the pre-activation method performed in both surfaces raised the EMG activity for all muscles: PM (p≤0.01), DA (p≤0.02), TB (p≤0.02) and SA (p≤0.03), and no differences were observed between stable and unstable conditions (p≥0.228). These results indicate that the execution of a previous exercise increases EMG activity. However, as there was no exclusive increase for primary agonist muscles, this increase cannot be attributed to the pre-activation method, but rather to the completion of two consecutive exercises.Key words: resistance training, electromyography, muscle strength, instability, shoulder